Severe Thrombocytopenia Caused by Vancomycin in the Intensive Care Unit: A Case Report - Li, Xiao-xiao; Wang, Guan-ru; Li, Chao; He, Na; Yao, Peng; Cheng, Yin-chu; Wang, Chu-hui; Ge, Qing-gang; Yi, Min; Wang, Zong-yu; Shi, Lu-wen; Zhao, Rong-sheng (Frontiers in Medicine, 2022)
Thrombocytopenia can cause substantial morbidity and mortality in critically ill patients. There are multiple etiology factors and various mechanisms associated with thrombocytopenia, of which drug-induced thrombocytopenia (DITP) deserves attention. Herein, we describe a case of severe thrombocytopenia during intensive care unit (ICU) hospitalization that was probable to be associated with vancomycin. By revealing the process of identifying this case of DITP and reviewing relevant clinical studies, a risk alert of vancomycin related severe hematotoxicity should be considered.